2003
DOI: 10.1554/0014-3820(2003)057[0766:icambf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Competition and Mating Between Fungal Strains of the Anther Smut Microbotryum Violaceum From the Host Plants Silene Latifolia and S. Dioica

Abstract: We studied intraspecific competition and assortative mating between strains of the anther smut fungus Microbotryum violaceum from two of its host species, Silene latifolia and S. dioica. Specifically, we investigated whether strains from allopatric host populations have higher competitive ability on their native host species and show positive assortative mating. In general, strains isolated from S. latifolia outcompeted strains isolated from S. dioica on both host species, but in female hosts, heterotypic dika… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…The full matrix of crosses was not performed because we could not obtain sporidia of both mating types for some species, probably due to mating‐type‐linked deleterious recessive mutations that occur commonly in lineages of this fungus (Hood and Antonovics 2000). Previous studies have shown that the addition of host extracts had no influence on the relative proportion of conjugations in vitro between different crosses (Kaltz and Shykoff 1999; Van Putten et al 2003), supporting a lack of this potential form of environmental influence. Sporidia were therefore suspended in 1 mL of sterile water.…”
Section: Methodsmentioning
confidence: 91%
“…The full matrix of crosses was not performed because we could not obtain sporidia of both mating types for some species, probably due to mating‐type‐linked deleterious recessive mutations that occur commonly in lineages of this fungus (Hood and Antonovics 2000). Previous studies have shown that the addition of host extracts had no influence on the relative proportion of conjugations in vitro between different crosses (Kaltz and Shykoff 1999; Van Putten et al 2003), supporting a lack of this potential form of environmental influence. Sporidia were therefore suspended in 1 mL of sterile water.…”
Section: Methodsmentioning
confidence: 91%
“…Studies have suggested a correlation between the rapidity of conjugation and competitive success (105). The developmental processes involved in mate recognition may therefore be of vital importance to the pathogen's life cycle.…”
Section: Mating-type Genes and Sex Chromosomesmentioning
confidence: 99%
“…S. latifolia flowers from April to October; its white flowers open and start emitting scent at dusk (Jurgens et al 1996). Nocturnal (moths) and diurnal (e.g., hoverflies) pollinators visit the plant (Jurgens et al 1996;Shykoff and Bucheli 1995;Van Putten et al 2003;Young 2002). The moth Hadena bicruris Hufnagel (Lepidoptera: Noctuidae) is considered to be the main pollinator in the European native range (Brantjes 1976;Jurgens et al 1996).…”
Section: Study Systemmentioning
confidence: 99%